Sistem Kendali Robot Beroda Wall-Follower pada Tembok Lurus dan Berbelok menggunakan Metode PID - Haryanto Sihombing; Eko Setiawan; Sabriansyah Rizqika Akbar (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2022)
Wall following navigation is one of the navigation systems used in competitions, for example, in the Indonesian Intelligent Robot Contest (KRCI), where the robot's task is to follow the contours of the walls that form hallways and rooms or is called a wall follower robot. The method used in this wall follower robot is PID method, can make system movement more stable and capable to do an effective error correction. PID controller can hold motor speed at required fixed value and navigate the wall follower. Arduino Uno R3 microcontroller, ultrasonic sensor, and L298N motor driver are used in making this robot system. The determination of the PID controller parameters was obtained using the Ziegler-Nichols second method. This method was chosen to anticipate changes in distance that cause oscillations in the ultrasonic sensor. The combination of PID and Ziegler-Nichols second method will speed up the process of determining PID controller parameters without having to go through a trial-and-error tuning process. The results of the tests showed that with the help of the PID controller, the wall follower robot has been able to make decisions about the movements that must be carried out to follow the side of the wall. The results of the PID parameters achieved from this final project research obtained values of Kp = 6, Ki = 17.1, and Kd = 0.525.